2013
DOI: 10.9790/3021-03623236
|View full text |Cite
|
Sign up to set email alerts
|

Detailed analysis of Speaker Recognition System and use of MFCCs for recognition

Abstract: -This paper presents the reader with the complete analysis of speaker recognition system with the explanation of each step with their necessity of existence. Every speaker recognition system comprises broadly of two phases namely the enrollment phase and the verification phase. The system in its first phase uses the record function for collecting the voices of different speakers and save them.Later these voices can be used to form a codebook and compare the voice with that in the enrollment phase. Enrollment p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…There is a good improvement in the accuracies for the emotion recognition system for Gender dependent and Gender independent experiments by using Linear -HMM with respect to i-vector. 4. From the experiments, it is observed that, Ergodic HMM has given better recognition performance than L-R HMM and i-vector.…”
Section: Fig 9: Comparision Of Recognition Accuracies For F-f Casementioning
confidence: 89%
“…There is a good improvement in the accuracies for the emotion recognition system for Gender dependent and Gender independent experiments by using Linear -HMM with respect to i-vector. 4. From the experiments, it is observed that, Ergodic HMM has given better recognition performance than L-R HMM and i-vector.…”
Section: Fig 9: Comparision Of Recognition Accuracies For F-f Casementioning
confidence: 89%